Essentials of Philosophical-Meditative Form Literature - Baltatu, Ludmila (Journal of Danubian Studies and Research, 2023)
Countless studies have been written about the role of belles-lettres in the formation of personality. We propose to approach in the following lines the literary works of a Romanian writer who is appreciated, at the due value, by the yesterday and nowadays readers – George Meniuc. As the author of poetry, prose writings, literary essays, translations, George Meniuc contributed substantially by his literary art to the promotion of our national beliefs. In this respect it is worth mentioning the variety of artistic approaches used by the writer in his pieces of literature, he being appreciated by the scientists in domain as one of the most valued authors of the short narrative genre. Namely in short-stories literary genre G. Meniuc’s aesthetic preferences are expressed alongside with clarity and analytical strength, special sensitivity and seductive power of his meditations on life and destiny in the light of Romanian traditions. As confirmation to the stated things would be the literary essay written by G. Meniuc, with a suggestive title Miorița. In this respect we’ll refer to a short passage from this literary writing with a deep philosophical-meditative character: “The Danube was glittering as a perch with scales in the sun, and, seized in a mesh of enchantment, as an ivy my being was whirling, I wanted to sing, to sip the Danube as dew, and love for life, faith in people, thirst for work, to turn all these into foliage, into flowers, into grass, into the murmur of water… As if I had crossed a border of life’s misteries”.